PERLINDUNGAN HUKUM PEKERJA ATAS PENAHANAN IJAZAH OLEH PERUSAHAAN - Okta Putri, Ni Putu Clara Devina; Senastri, Ni Made Jaya; Antaguna, Nyoman Gde (Jurnal Ilmiah Dinamika Hukum, 2026)
ABSTRACT There must be a fair and balanced application of the legal rights and responsibilities that arise from the employment relationship between employers and employees. Employers' continued activities of withholding diplomas from workers, even after the employment relationship has ended, may have negative consequences for workers and limit their ability to find new career possibilities. The purpose of this research is to examine the employment agreement's provisions on the parties' respective roles and responsibilities in the workplace, and to determine whether or not employees have any recourse if their employers choose to retain their diplomas even after the job relationship has ended. Normative legal research using conceptual, factual, and regulatory approaches is the study technique used. Holding workers' diplomas is illegal, violates their human rights, and goes against labor laws and regulations, according to the report. Legislation protects employees both preemptively, via government oversight and normative regulation, and punitively, via processes for resolving disputes in industrial relations and the imposition of administrative, civil, and criminal penalties. Companies cannot legitimately withhold diplomas; thus, this practice must end in order to provide legal clarity and respect for workers' dignity. Keywords : Legal Protection, Workers, Diploma.